The National Falls and Bone Health Audit: implications for UK emergency care. Issue 10 (1st November 2011) - Banerjee, Jay; Benger, Jonathan; Treml, Jonathan; Martin, Finbarr C; Grant, Rob; Lowe, Derek; Potter, Jonathan; Husk, Janet
Abstract : Introduction: The National Clinical Audit of Falls and Bone Health, coordinated by the Royal College of Physicians, assesses progress in implementing integrated falls services across the UK against national standards and enables benchmarking between service providers. Nationally, falls are a leading contributor towards mortality and morbidity in older people and account for 700 000 visits to emergency departments and 4 million annual bed days in England alone. Methods: Two rounds of national organisational audit in 2005 and 2008 and one national clinical audit in 2006 were carried out based on indicators developed by a multidisciplinary group. Results: These showed that management of falls and bone health in older people remains suboptimal in emergency departments and minor injury units and opportunities are being missed in carrying out evidence-based risk assessment and management. Conclusions: Older people attending emergency departments in the UK following a fall are receiving a poor deal. There is an urgent need to ensure more effective assessment and management to prevent further falls and fractures.